2021
DOI: 10.3389/fgene.2021.813873
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of Long Non-coding RNA and Related Diseases: An Overview

Abstract: Long non-coding RNAs (lncRNAs) are usually located in the nucleus and cytoplasm of cells. The transcripts of lncRNAs are >200 nucleotides in length and do not encode proteins. Compared with small RNAs, lncRNAs have longer sequences, more complex spatial structures, and more diverse and complex mechanisms involved in the regulation of gene expression. LncRNAs are widely involved in the biological processes of cells, and in the occurrence and development of many human diseases. Many studies have shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…In hyperglycemia, transfection of Gm10451 siRNA into islet β- cells inhibited the expression of Gm10451 and reversed those changes before. In addition, diabetes is closely linked to oxidative stress, which causes an excess of free radicals such as reactive oxygen species and is responsible for the dynamic imbalance between oxidative and antioxidant systems, which causes inflammation and damage to pancreatic tissue; then reduces the activity of SOD, an important antioxidant enzyme that scavenge oxygen free radicals, exacerbates inflammation and ultimately leads to apoptosis and damage of MIN6 cells ( Gong et al, 2021 ; Kim et al, 2021 ; Sultan et al, 2021 ). Our results were sufficient to prove that hyperglycemia promotes ROS production and reduces SOD activity of islet β cells; whereas, in this environment, a downregulation to the Gm10451 expression in pancreatic β-cells improves SOD activity, suppresses ROS content, and alleviates oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In hyperglycemia, transfection of Gm10451 siRNA into islet β- cells inhibited the expression of Gm10451 and reversed those changes before. In addition, diabetes is closely linked to oxidative stress, which causes an excess of free radicals such as reactive oxygen species and is responsible for the dynamic imbalance between oxidative and antioxidant systems, which causes inflammation and damage to pancreatic tissue; then reduces the activity of SOD, an important antioxidant enzyme that scavenge oxygen free radicals, exacerbates inflammation and ultimately leads to apoptosis and damage of MIN6 cells ( Gong et al, 2021 ; Kim et al, 2021 ; Sultan et al, 2021 ). Our results were sufficient to prove that hyperglycemia promotes ROS production and reduces SOD activity of islet β cells; whereas, in this environment, a downregulation to the Gm10451 expression in pancreatic β-cells improves SOD activity, suppresses ROS content, and alleviates oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are a kind of noncoding RNAs (ncRNA) with a length >200 nucleotides which are currently the primary and most concerned ncRNAs together with the microRNA (miRNA) and circle RNA (circRNA) in cancer research. Report has showed that lncRNAs may be involved in more diverse and complex mechanisms to regulating more biogenetic process because of the longer sequences and more complex spatial structures compared with small RNAs ( 15 ). Thus, there are more potential lncRNAs to be found as the biomarkers of specific diseases including lung cancer based on a better understand of their vast and complex roles in their pathological regulation.…”
Section: Overview Of the Lung Cancer Screening Methodsmentioning
confidence: 99%
“…With the development of bioinformatics technology, studying the function and regulation mechanism of genes to find drug targets has become the mainstream direction of medical treatment now. 12,13 By means of bioinformatics, we found that genetic changes between different biological states could serve as potential therapeutic measures for DMED. 14,15 In this article, transcriptome data of normal and DMED rats were obtained from gene expression omnibus (GEO; https://www.ncbi.nlm.nih.gov/gds) GSE2457 dataset.…”
Section: Introductionmentioning
confidence: 99%